Strategies to influence RN specialty certification. Issue 8 (August 2016) - Solomon, Deborah; Lahl, Meredith; Soat, Marian; Bena, James; McClelland, Mark
Abstract : Learn how you can increase nurses' likelihood to certify by removing the barriers identified in this study.